Decision Support System for Selecting Business and Industrial Partners (DUDI) for Industrial Internship Placement Using the Simple Additive Weighting (SAW) Method at SMK Negeri 1 Barus Utara - Kristian Siregar; Riswan Limbong; RL. Harmadi Tamba; Monang Juanda Tua Sihombing (Pascal: Journal of Computer Science and Informatics, 2026)
Vocational High Schools (SMKs) play a strategic role in producing graduates who are competent, skilled, and prepared to meet the demands of the industrial workforce. One of the core programs designed to achieve this objective is the Industrial Internship Program (Praktik Kerja Industri/Prakerin), which enables students to apply the theoretical knowledge acquired in the classroom to real workplace environments. However, selecting appropriate Business and Industrial Partners (Dunia Usaha dan Dunia Industri—DUDI) remains a challenging task due to the involvement of multiple evaluation criteria, including curriculum compatibility, industrial facilities, accessibility, accommodation costs, and partner reputation. At SMK Negeri 1 Barus Utara, the selection process is still conducted manually, making it susceptible to subjectivity and inconsistency. This study proposes a Decision Support System (DSS) employing the Simple Additive Weighting (SAW) method to objectively rank potential DUDI partners based on predefined evaluation criteria and their corresponding weights. The research adopts a quantitative approach within the Multi-Criteria Decision Making (MCDM) framework. Five assessment criteria were established through interviews with internship coordinators, and five DUDI partners were evaluated as alternatives. The findings indicate that PT Sibolga Citra Komputindo achieved the highest preference score (0.7700), making it the most suitable internship partner. The implementation of the SAW method demonstrates its effectiveness in producing objective, transparent, and measurable recommendations, thereby improving the quality of internship management and supporting informed decision-making in vocational education.